Myocardial Apelin Production is Reduced in Humans With Left Ventricular Systolic Dysfunction - Chandrasekaran, Badrinathan; Kalra, Paul R.; Donovan, Jackie; Hooper, James; Clague, Jonathon R.; McDonagh, Theresa A. (Journal of cardiac failure, 2010)
Apelin is a novel endogenous peptide with inotropic and vasodilatory properties that is the ligand for the APJ receptor. Apelin and APJ are widely distributed in the vasculature of a number of organs and peripheral venous apelin is reduced in heart failure (HF). The location of apelin production in humans with and without HF was investigated. Plasma apelin and brain natriuretic peptide (BNP) concentrations in coronary sinus (CS), aorta (Ao), and renal vein (RV) of individuals with HF (n = 9) were compared to subjects with normal structural hearts (n = 8). In HF the concentration of CS apelin was reduced compared with controls (310 pg/mL [interquartile range 290-390] vs. 470 pg/mL [340-570], P < .035) but Ao apelin (330 pg/mL [275-375] vs. 340 pg/mL [230-455], P = .76) and RV apelin (290 pg/mL [280-360] vs. 370 pg/mL [273-410], P = .56) were unchanged. Plasma BNP was increased at all sampling sites in patients with HF as compared with controls. A step down from CS to Ao to RV in all subjects was observed. The step down in apelin from CS to Ao (470 pg/mL [310-595] vs. 320 pg/mL [225-482], P < .04) in control subjects was not apparent in patients with HF. These novel data show that apelin is produced in the human heart and that production is reduced in individuals with HF. In contrast to BNP, apelin production is not exclusive to the heart.